Analysis of Fulfillment of Navigation Equipment on Motor Sailing Ship on Safety Ship Safety The flag of Indonesia (Case Study of Makassar Potere Port) - Hadi Setiawan; Eva Susanti; Poerwanto Poerwanto (Trunojoyo University of Madura, 2022)
In the development of shipping, the national frequency has increased quite significantly. However, the rate of ship accidents and incidents that occur in Indonesian waters has also increased. Developing countries including Indonesia have not succeeded in reducing the number of sea transportation accidents . This study aims to analyze the readiness of the fulfillment of navigation tools on motor sailing vessels to the safety of shipping on Indonesian-flagged vessels and describe how much influence the readiness of the fulfillment of navigation tools on motor sailing vessels has on the safety of shipping on Indonesian-flagged vessels. Quantitative research method using a survey approach. The analysis technique used is regression analysis and correlation analysis. The results showed that there was an influence of readiness to fulfill navigational equipment on motor sailing vessels affecting shipping safety on Indonesian-flagged ships (p value 0.000 0.05) and 53.2% of the effect, while 46.8 % was determined by other variables outside of this study. There is a need for further research on the influence of other factors from motor sailing vessels on shipping safety on Indonesian-flagged vessels.